Les peintures postglaciaires en Provence Inventaire. Étude chronologique, stylistique et iconographique - Hameau, Philippe (Documents d'archéologie française, 1989)
The author's work constitutes the first synthesis, since Father Glory's work published in 1948, about an unknown aspect of Prehistoric art : postglacial symbolic paintings. This is an inventory ot the Provence painted sites made after systematic surveys which led to rectify interpretation and location mistakes and to put the sites in their archaeological context. This is also an approach to the delicate questions of datation, typology and interpretation. This work appears as a critical study and a documentary corpus necessary to keep in memory these Neolithic art witnesses which disappear more and more every year because of natural agents and vandalism.